2010
DOI: 10.1111/j.2042-3292.2010.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular findings in healthy newborn foals according to age

Abstract: Summary The aim of this prospective observational clinical study was to carry out a descriptive ophthalmic investigation in healthy newborn foals for the establishment of normal ocular anomalies found during the whole neonatal period. To date there have been no studies specifically addressing the normal ocular findings and variations of the eye and adnexa in foals during the neonatal period. Knowledge of the ocular characteristics at this early age will help equine practitioners to better identify ocular abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
1
11
1
Order By: Relevance
“…A recent study suggested that IOP may decrease with age also in miniature donkeys 22 . Newborn foals have been reported to have IOP readings similar to adult horses 27,28 . While in this study, IOP was not found to be associated with age, all of the horses were adults and only two were older than 15 years (data not shown).…”
Section: Discussioncontrasting
confidence: 60%
“…A recent study suggested that IOP may decrease with age also in miniature donkeys 22 . Newborn foals have been reported to have IOP readings similar to adult horses 27,28 . While in this study, IOP was not found to be associated with age, all of the horses were adults and only two were older than 15 years (data not shown).…”
Section: Discussioncontrasting
confidence: 60%
“…Menace responses were inconsistent in newborn foals in accordance with what has been described in normal foals during the first weeks of life. [21][22][23] Two positive wavelets (P2 and P4) and two negative wavelets (N1 and N2) were identified in all FVEP recordings, while additional wavelets (P1, N2a, P3, and P5) were observed in some recordings in accordance with what was seen in our previous study. 19 There were no specific differences when comparing tracings between age groups in this aspect.…”
Section: Resultssupporting
confidence: 90%
“…32 However, a normal menace response is often not seen until up to 2 weeks postpartum, whereas subcortical reflexes, such as the pupillary light and dazzle reflexes, are present at birth in the foal. [21][22][23] We found that all newborn foals included in the study lacked normal menace responses, although their FVEP waveforms appeared mature-like. It is known that the efferent pathway of the menace response is conveyed through cerebellum and facial neurons in the brainstem, 33 and the lack of menace response may also depend on the immature cerebellum in the newborn foal rather than an immature input to or processing in the visual cortex alone.…”
Section: T a B L E 1 Flash Visual Evoked Potentials (Fveps) In Newbormentioning
confidence: 77%
See 1 more Smart Citation
“…A comprehensive evaluation of these ocular features is paramount when examining the neonate 1 . The neonatal pupil is initially round in shape 2,3 and becomes horizontal and elliptical throughout the first week of life 3,4 . The globe of many foals shows a mild ventromedial orientation at birth 3 but acquires a normal position after several days 3 or even later 5 .…”
Section: Introductionmentioning
confidence: 99%